Implementing Biology Learning with a Differentiated Approach to Support Students 21st Century Skills Independent Curriculum - Nasrianus Sera; Anggi Tias Pratama; Devi Mayuko Saragih (Jurnal Penelitian Pendidikan IPA, 2025)
In the context of implementing the independent curriculum, a differentiated learning approach is an important strategy by giving freedom to teachers and learners. This research aims to analyze various learning models, media, and the impact of implementing biology learning with a differentiated approach to support 21st century skills. The method used is a systematic analysis that follows the PRISMA guidelines. The results showed that the implementation of biology learning based on a differentiated approach can support critical thinking, creativity, collaboration, and effective communication skills. The applied learning model includes PBL (Problem Based Learning), PjBL (Project Based Learning), and DL (Discovery Learning), each of which supports content, process, and product differentiation. The learning media used include teaching modules, puzzles, images, educational videos, canva, worksheets, presentation slides, audio, and posters. Thus, the application of appropriate learning models and media in Biology learning in accordance with the diversity and learning needs of students has a positive impact on the development of students' 21st century skills, such as problem analysis, exploration, solutions, and effective communication.